2008
DOI: 10.1093/bja/aen038
|View full text |Cite
|
Sign up to set email alerts
|

Role of routine chest radiography after percutaneous dilatational tracheostomy

Abstract: Immediate CXR after uncomplicated PDT performed under bronchoscopic guidance rarely reveals unexpected radiological abnormalities. The role of CXR after PDT appears to be restricted to those patients undergoing technically difficult and complicated procedures. A change in practice to this effect will lead to reductions in both medical costs and exposure of staff and patients to ionizing radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
(6 reference statements)
2
19
0
2
Order By: Relevance
“…A chest X-ray after the procedure did not show any complication related to the procedure and therefore, in agreement with previous studies, we state there is no indication for a routine chest X-ray after an uneventful PDT [21]. Swallowing problems are common after endotracheal intubation [22].…”
Section: Discussionsupporting
confidence: 89%
“…A chest X-ray after the procedure did not show any complication related to the procedure and therefore, in agreement with previous studies, we state there is no indication for a routine chest X-ray after an uneventful PDT [21]. Swallowing problems are common after endotracheal intubation [22].…”
Section: Discussionsupporting
confidence: 89%
“…Of the 40 cases with complications detected on chest X‐ray, five had post‐procedural signs and symptoms, while two were asymptomatic. Unfortunately, there was no documentation of the remaining 33 cases . However, of the seven cases that were documented, the three cases which required intervention (chest tube) all presented post‐procedurally with clinical signs and symptoms, while none of the two asymptomatic cases required any intervention. Bronchoscopic guidance .…”
Section: Resultsmentioning
confidence: 99%
“…Kumar et al 19 studied the role of CXR after PDT and concluded that CXR had no changes after non-complicated PDT under the guide of bronchoscopy. Therefore, it seems that the roll of CXR after PDT is limited to those with technical difficulties.…”
Section: Discussionmentioning
confidence: 99%